Hubungan Dukungan Suami, Peran Bidan Dan Sumber Informasi Terhadap Kepatuhan Ibu Hamil Dalam Pemeriksaan HBsAg Di Puskesmas Cikedal Tahun 2022 : The Relationship of Husband Support, the Role of the Midwife and Sources of Information on the Compliance of Pregnant Mothers in HBsAg Audit in Cikedal Puskesmas in 2022 - Hanurawati, Tati (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: HBsAg examination is important to detect Hepatitis B in pregnant women, so it needs to be done during the first visit to health workers, as an effort to prevent and control the disease. Methods: This study used an observational analytic method with a cross-sectional study design and used the chi-square test. The sampling technique was carried out by side total with a total sample of 118 people. Results: The results showed that there was a relationship between husband's support (p-value = 0,000 and OR = 5,023), the role of the midwife (p-value = 0,018 and OR = 2,436), and sources of information (p-value = 0,004 and OR = 3,707) with compliance. pregnant women in HBsAg examination. It was concluded that there was a relationship between the husband's support, the role of midwives, and sources of information with pregnant women's compliance in the HBsAg examination at the Cikedal Health Center in 2022. Discussion: It is hoped that the Cikedal Health Center will provide an appeal to doctors, midwives, and other health workers to encourage the public to carry out HBsAg examinations and carry out HBsAg examinations as well as possible. in the first trimester and repeated in each trimester.